Controlled crystallization of metastable polymorphic pharmaceutical: Comparative study of batchwise and continuous tubular crystallizers. (2nd February 2023) - Fang, Lan; Gao, Zhenguo; Gao, Zhenjie; Huang, Wenfeng; Wan, Xuxing; Rohani, Sohrab; Gong, Junbo
Graphical abstract: The metastable crystal Form III of APZ was successfully produced using a continuous and controllable tubular cooling crystallization method with the assistance of ultrasound and air segmented slug flow process, while in batch crystallizers, the crystal form cannot be controlled due to uneven temperature and concentration distribution. Highlights: Pure metastable Form III could be prepared consistently through tubular crystallization rather than batch crystallization. Applying ultrasound and air segment solved the fouling problem in flow crystallization process. The flow crystallization enabled a yield of 90.6% along with the desired polymorphic form. The Fluent simulations revealed the uneven distribution of temperature and concentration in the batch crystallizer. Abstract: The deliberate and reproducible crystallization of metastable polymorphs of active pharmaceutical ingredients (APIs) from solution remains difficult and is still far from trivial. The main challenge is to prevent cross nucleation of the stable form. The traditional cooling experiments in a batch crystallizer cannot repeatably produce aripiprazole (APZ) metastable Form III within selected initial concentrations and cooling rates. The computational fluid dynamics simulations confirmed that fluctuations in temperature and solution concentration in the batch crystallizer would induce the nucleation of stable crystal forms and accelerate solvent-mediated phase transformation. This work presents, for the first time, ultrasonic- and slug-assisted tubular crystallizers for the continuous and controllable preparation of pure metastable crystal Form III of APZ. The ultrasound-assisted air segmented plug flow tubular crystallizer provides an efficient configuration to produce high purity metastable polymorphism pharmaceuticals, which also offers a facile approach for the continuous manufacturing of drug substances.